The effectiveness of development finance institutions in South Africa in relation to Small and Medium Enterprises (SMEs) - Xaba, Nonkosi (My University, 2022)
With dire economic challenges in South Africa and understanding that Small and Medium Enterprises (SMEs) can play a role in fostering economic growth, there was a need to understand the effectiveness of state-owned Development Finance Institutions (DFIs). This was due to DFIs being mandated to assist SMEs access finance, since they tend to be excluded from traditional financiers. The main objective of this research was to uncover facts around the effectiveness of DFIs in relation to their mandate to support Small and Medium Enterprises. The study adopted a qualitative research methodology to achieve these objectives, using interviews as a data collection method and thematic analysis for data analysis. It was found that there were challenges with the process of accessing finance where DFIs were stringent and lengthy with their internal processes, which prioritized ensuring that SMEs were able to service the debt facility. Although DFIs provided business support to aid SMEs, the level of support was perceived to be misaligned with the specific needs of the SME. These findings led to the conclusion that state-owned DFIs in South Africa are moderately effective in relation to SMEs and only support SMEs to a limited extent. It was recommended that, to balance out the sustainability of DFIs without abandoning the development objectives; DFIs together with the government, can agree on a specific capital adequacy ratio (CAR). This allows for some flexibility within the DFIs internal processes so that they are not long or stringent because the focus is on being profitable
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in n Finance and Investments to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Financial Institutions; Small and Medium Enterprises (SMEs); South Africa; UCTD; SDG-8: Decent work and economic growth